Recent Advance on Mesoporous Silica Nanoparticles-Based Controlled Release System: Intelligent Switches Open up New Horizon - Sun, Ruijuan; Wang, Wenqian; Wen, Yongqiang; Zhang, Xueji (Nanomaterials (Basel, Switzerland), 2015)
Mesoporous silica nanoparticle (MSN)-based intelligent transport systems have attracted many researchers’ attention due to the characteristics of uniform pore and particle size distribution, good biocompatibility, high surface area, and versatile functionalization, which have led to their widespread application in diverse areas. In the past two decades, many kinds of smart controlled release systems were prepared with the development of brilliant nano-switches. This article reviews and discusses the advantages of MSN-based controlled release systems. Meanwhile, the switching mechanisms based on different types of stimulus response are systematically analyzed and summarized. Additionally, the application fields of these devices are further discussed. Obviously, the recent evolution of smart nano-switches promoted the upgrading of the controlled release system from the simple “separated” switch to the reversible, multifunctional, complicated logical switches and selective switches. Especially the free-blockage switches, which are based on hydrophobic/hydrophilic conversion, have been proposed and designed in the last two years. The prospects and directions of this research field are also briefly addressed, which could be better used to promote the further development of this field to meet the needs of mankind.